Cultural Aesthetic Mediation as a Resilience Strategy: A Study of Representational Communication in the Betawi Cultural Village of Setu Babakan - Ferdiansyah Ali; Sunarmi Sunarmi; Titis Srimuda Pitana; Budi Setiyono (International Journal Labs, 2025)
Urbanization, globalization, and the intensification of cultural tourism have placed Betawi cultural arts in a vulnerable position amid changes in meaning, commodification, and shifts in aesthetic values. This study aims to explain how cultural aesthetics are mediated as a resilience strategy through representational practices in the Betawi Cultural Village (PBB) Setu Babakan. Using a phenomenological approach and representation theory, it examines how aesthetic experiences—in visual, narrative, and ritual forms—are created, negotiated, and interpreted by cultural actors, including government officials, local communities, and tourists. The analysis was conducted through field observations, in-depth interviews, visual documentation, and hermeneutic interpretations based on Bourdieu's theory of habitus, cultural capital, and the arena of cultural production. The results show that aesthetic mediation functions as a connecting mechanism between traditional values and the demands of the tourism industry, yielding three main processes: creative reproduction, representational transformation, and authenticity negotiation. These processes enable Betawi culture to survive and adapt without losing its essential dimensions of meaning. The findings contribute to the development of cultural tourism studies, cultural communication design, and representation theory in the context of Indonesian urban society.